2016
DOI: 10.1111/1471-0528.13949
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and occupational variation of ovarian granulosa cell tumours in Finland, Iceland, Norway and Sweden during 1953–2012: a longitudinal cohort study

Abstract: Objective To determine the incidence and occupational variation of granulosa cell tumours (GCTs) in Finland, Iceland, Norway and Sweden over a 60-year period, 1953-2012. Design A longitudinal cohort study.Setting and population Finland, Iceland, Norway and Sweden and a total of 249 million women over a 60-year period . The NOCCA (Nordic Occupational Cancer Study) included 6.4 million women with 776 incident GCT cases diagnosed until the end of follow up.Methods Incidence rates were calculated from the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…According to the 2014 World Health Organization histological classification of ovarian tumors, ovarian granulosa cell tumors are divided into two types: ovarian adult granulosa cell tumor (AGCOT) and ovarian juvenile granulosa cell tumor (JGCOT) [2]. Ovarian adult granulosa cell tumor, accounting for 95% of ovarian granulosa cell tumor, mainly occurs in perimenopausal and postmenopausal women and exhibits unpredictably late recurrence features [3][4][5][6]. Among the multiple prognostic factors reported, menopause, tumor diameter, estrogen and CA125 levels, International Federation of Gynecology and Obstetrics (FIGO) staging, residual lesions, multisite recurrence, and presence of mitotic figures have been mentioned as factors associated with the prognosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2014 World Health Organization histological classification of ovarian tumors, ovarian granulosa cell tumors are divided into two types: ovarian adult granulosa cell tumor (AGCOT) and ovarian juvenile granulosa cell tumor (JGCOT) [2]. Ovarian adult granulosa cell tumor, accounting for 95% of ovarian granulosa cell tumor, mainly occurs in perimenopausal and postmenopausal women and exhibits unpredictably late recurrence features [3][4][5][6]. Among the multiple prognostic factors reported, menopause, tumor diameter, estrogen and CA125 levels, International Federation of Gynecology and Obstetrics (FIGO) staging, residual lesions, multisite recurrence, and presence of mitotic figures have been mentioned as factors associated with the prognosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Granulosa cell tumors (GCTs) of the ovary are very rare, and account for less than 5% of all ovarian malignancies [1,2]. Bryk et al found that the incidence of granulosa cell tumors was very low -0.6 to 0.8 per 100000 for their study period [3]. These tumors can be further divided into two distinct subtypes (juvenile GCTs and adult GCTs (aGCTs)) on the basis of their histologic, biochemical and molecular features.…”
Section: Introductionmentioning
confidence: 99%
“…From the cancer databases in Finland, Iceland, Norway and Sweden, the GCT onset showed scattered feature. There was no increasing trend over the 60 years [ 5 ]. Abnormal cell cycle is related to the occurrence and development of cancers.…”
Section: Introductionmentioning
confidence: 99%